Alexithymia in obese adolescents is associated with severe obesity and binge eating behavior1 - Susane Fanton; Luciane Coutinho Azevedo; Deisi Maria Vargas (Elsevier, 2022)
Objective: To study the occurrence of alexithymia in obese adolescents. Methods: Cross-sectional study with 102 obese adolescents. Sociodemographic, clinical, and psychometric data (alexithymia and binge eating) were analyzed The Brazilian version of the Toronto Alexithymia Scale and Binge Eating Scale were used for psychometric data collection. Statistical analysis was performed using the Kolmogorov-Smirnov test, Student's t-test, ANOVA, chi-square, linear regression, and logistic regression. The study was approved by Research Ethics Committee. Results: A 22% occurrence of alexithymia was observed. Considering the category "possible alexithymia", half of the participants presented some alexithymic behavior. Adolescents with alexithymia had higher binge eating scores (alexithymia 16,2 versus possible alexithymia 11,7 versus no alexithymia 8,5; ANOVA p < 0,0005) and three times more binge eating behavior than adolescents with no alexithymia or possible alexithymia (alexithymia 36.4% versus 17.2% possible alexithymia versus 11.8% no alexithymia; chi-square = 6,2, p = 0.04). In simple linear regression, alexithymia scores were positively associated with binge eating scores (r2 = 0,4; p = 0,002). Binary logistic regression showed a three times higher probability of an adolescent with severe obesity to meet the criteria for alexithymia. Conclusions: There was a 22% occurrence of alexithymia in obese adolescents. It was positively associated with obesity severity and higher binge eating scores, suggesting a relationship between severe obesity, alexithymia, and binge eating behavior.